2020
DOI: 10.3390/ani10091686
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Broiler Chickens to Dietary Soybean Meal Reduction with Glycine and Cysteine Inclusion at Marginal Sulfur Amino Acids (SAA) Deficiency

Abstract: The responses of broiler chickens to dietary protein reduction were investigated in the presence of glycine and cysteine inclusion at the marginal deficiency of sulfur-containing amino acids. A total of 432 broiler chickens were allotted to six dietary treatments; SP1 is standard protein diet with 100% total sulfur amino acids (TSAA), SP2 is standard protein diet with 85% TSAA, RP is reduced protein diet without glycine and cysteine supplementation, RPC is reduced protein diet with cysteine supplementation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In experiment 2, birds fed the LCP88 diet had greater absolute and relative fat pad weights than the CTL or RCP group, and increasing the concentration of tGly + Ser linearly reduced abdominal fat deposition, though the lowest relative fat pad weight of all the LCP groups was still 16% higher than that of the CTL group. These results are in agreement with Elahi et al (2020) who showed that supplementing Gly in reduced CP diets can lower fat pad deposition, but not to the level of control-fed broilers. Increasing dietary Gly or betaine (trimethylglycine) has been demonstrated to stimulate lipid oxidation and reduce fat deposition in poultry, rats, and swine ( El Hafidi et al, 2004 ; Fouad and El-Senousey, 2014 ; Zhong et al, 2021 ); however, the role of Gly on broiler lipid metabolism needs further elucidation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In experiment 2, birds fed the LCP88 diet had greater absolute and relative fat pad weights than the CTL or RCP group, and increasing the concentration of tGly + Ser linearly reduced abdominal fat deposition, though the lowest relative fat pad weight of all the LCP groups was still 16% higher than that of the CTL group. These results are in agreement with Elahi et al (2020) who showed that supplementing Gly in reduced CP diets can lower fat pad deposition, but not to the level of control-fed broilers. Increasing dietary Gly or betaine (trimethylglycine) has been demonstrated to stimulate lipid oxidation and reduce fat deposition in poultry, rats, and swine ( El Hafidi et al, 2004 ; Fouad and El-Senousey, 2014 ; Zhong et al, 2021 ); however, the role of Gly on broiler lipid metabolism needs further elucidation.…”
Section: Discussionsupporting
confidence: 92%
“… Hofmann et al (2019) found Glu, Pro, Asn, and Gln plasma concentrations increased with increased tGly + Ser levels, but several other plasma AA concentrations interacted with Gly and CP levels. Although not evaluated in this study, metabolic intermediates such as the ones studied by Elahi et al (2020) and Hofmann et al (2019) could further our understanding of the upregulation or downregulation of certain pathways in response to Gly, Ser, Met, and Cys relationship and this should be considered in future studies. A limitation of the current study is that we were not able to collect blood from birds in the control groups (CTL and RCP) for comparison due to their use in another concurrent experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In broilers, ref. [ 40 ] also observed that by increasing the content of sulphur amino acids from 85% to 100% above requirements (using dietary supplementation with synthetic DL-methionine), the birds showed an increased content of cysteine in plasma, amongst other amino acids. Cysteine intestinal transport involves two carrier-mediated processes [ 41 ] that are selectively inhibited by other amino acids with small polar side chains (such as threonine) or large non-polar side chains (such as methionine).…”
Section: Discussionmentioning
confidence: 99%
“…The AMEn-to-CP ratio of LP diets was nearly the same, but only the LP3 treatment resulted in a significant increase in the abdominal fat pad ratio. The use of synthetic Gly supplementation can reduce the fatness of broilers fed LP diets ( 37 , 54 , 55 ). According to studies with poultry, rats, and swine, increasing dietary Gly or betaine (trimethylglycine) has been demonstrated to stimulate lipid oxidation and reduce plasma concentrations of triglycerides and fat deposition ( 56–58 ).…”
Section: Discussionmentioning
confidence: 99%